A Produção biopolítica do corpo saudável: mídia e subjetividade na cultura do excesso e da moderação - Dantas, Eduardo Ribeiro (2007)
Recognizing the plans left by Foucault as legitimate, for those that the struggle to fight against all forms of way of life subjection takes an important role on human being existence, this thesis questions the impacts of body planning on health specialized media on the production of the contemporary subjectivity. Having the Saúde! magazine as this thesis empirical field, it discusses the subjectivity processes centered on the realization of many bodily practices destined to a perfect body self-construction, finding suitable conditions for a narcissistic development of the new ways of social regulation on hypermodern societies. Our central argument, refering to a specific reflection about the body, media and subjectivity, is that the body promoting over the health specialized media makes possible the creation of new existential territories, configuring the healthy body bio-political production by a subjectivity process open to experimenting and to self-invention. Bodily subjectivity process centered on body self-construction, simultaneously generating human subjectivity singularization and massification, evidencing escape routes to build a body health existential perspective. In this thesis we seek to point not only the historically hegemonic forms of being healthy, but mainly the forces that nowadays question these forms, making possible the thought of other ways to live the health of the body, starting from the subjectivity singularization